Bullous pemphigoid after Split Skin grafting in vitiligo patient - Siddharth Bhatt; Anand Mannu; Gourang Paliwal; Biju Vasudevan (Pigment International)
Bullous pemphigoid (BP) is an autoimmune condition characterized by tense subepidermal blisters commonly seen in old age. Vitiligo is another autoimmune disease associated with loss of melanocytes. Very few cases of coexistence of vitiligo and BP are reported. A split skin graft (SSG) is a surgical option for stable vitiligo. BP over the SSG is a rare occurrence. We present the case of an elderly individual who developed BP at the site of SSG for vitiligo. Postmanagement of BP the lesion healed with recurrence of vitiligo patch at the same site. This case highlights that surgical intervention without ascertaining the stability of the disease activity may not only preclude the patient to the development of the primary disease but also lead to development of other autoimmune illnesses at the surgical site due to unmasking of the epitope to already circulating antibodies.